An Empirical Investigation of the Strategic Use of Debt - Pettersson‐Lidbom, Per (Journal of Political Economy, 2001)
The paper examines the accumulation of debt by Swedish local governments. I find that right‐wing governments accumulate more debt when facing a higher probability of defeat, whereas the opposite occurs for left‐wing governments. These effects are sizable: a right‐wing government increases its level of debt by 15 percent, whereas a left‐wing government decreases its debt by 11 percent if they are both certain of being replaced as compared to when they are certain of remaining in office. The results are consistent with the predictions from a strategic debt model developed by Persson and Svensson.